Isotopic constraints on the genesis and evolution of basanitic lavas at Haleakala, Island of Maui, Hawaii. (15th December 2016) - Phillips, Erin H.; Sims, Kenneth W.W.; Sherrod, David R.; Salters, Vincent J.M.; Blusztajn, Jurek; Dulai, Henrietta
Abstract: To understand the dynamics of solid mantle upwelling and melting in the Hawaiian plume, we present new major and trace element data, Nd, Sr, Hf, and Pb isotopic compositions, and 238 U– 230 Th– 226 Ra and 235 U– 231 Pa– 227 Ac activities for 13 Haleakala Crater nepheline normative basanites with ages ranging from ∼900 to 4100 yr B.P. These basanites of the Hana Volcanics exhibit an enrichment in incompatible trace elements and a more depleted isotopic signature than similarly aged Hawaiian shield lavas from Kilauea and Mauna Loa. Here we posit that as the Pacific lithosphere beneath the active shield volcanoes moves away from the center of the Hawaiian plume, increased incorporation of an intrinsic depleted component with relatively low 206 Pb/ 204 Pb produces the source of the basanites of the Hana Volcanics. Haleakala Crater basanites have average ( 230 Th/ 238 U) of 1.23 ( n = 13), average age-corrected ( 226 Ra/ 230 Th) of 1.25 ( n = 13), and average ( 231 Pa/ 235 U) of 1.67 ( n = 4), significantly higher than Kilauea and Mauna Loa tholeiites. U-series modeling shows that solid mantle upwelling velocity for Haleakala Crater basanites ranges from ∼0.7 to 1.0 cm/yr, compared to ∼10 to 20 cm/yr for tholeiites and ∼1 to 2 cm/yr for alkali basalts. These modeling results indicate that solid mantle upwelling rates and porosity of the melting zone are lower for Hana Volcanics basanites than for shield-stage tholeiites from Kilauea and Mauna Loa and alkali basalts from Hualalai. The melting rate, which is directly proportional to both the solid mantle upwelling rate and the degree of melting, is therefore greatest in the center of the Hawaiian plume and lower on its periphery. Our results indicate that solid mantle upwelling velocity is at least 10 times higher at the center of the plume than at its periphery under Haleakala.